Proteção constitucional do consumidor no âmbito da regulação publicitária - Alves, Fabrício Germano (2011)
The concern with issues related to consumer protection has emerged in North America and then spread throughout the world. In Brazil, consumer‟s rights and interests only gained greater importance after their consolidation in the Constitution of 1988 and the enactment of the 8078/90 Law (Consumer‟s Protection and Defense Code), which established the consumerist microsystem. The understanding of the legal relationship of consumption concept is necessarily connected to knowledge of the elements that compose it. Among these, we can find the consumer and the provider (subjective elements), the product or service (objective elements), and the consumer‟s condition as final receiver of the consumption object (finalistic element). In order to elucidate the configuration of consumer protection before advertising communication, this work will analyze the advertising through the prism of consumerist laws, conceptualizing it and presenting a differentiation of it in relation to practices such as marketing, offer and commercial communication as well as examining its several kinds of manifestation, focusing mainly the ones categorized as misleading or unfair advertising. All kinds of advertising communication against the consumerist microsystem are subject to judicial control exercised by the State. Besides individual protection possibilities, this state-owned control can be collectively exercised as a result of the utilization of public civil action and popular action. Some specific categories of advertising (smoking products, alcoholic beverages, pesticides, medicines and therapies) are still subject to a set of particular restraints provided by the 9294/96 Law, which enables the performance of a special control in relation to them. In addition to state control, there is also a system of advertising communication self-regulation, which develops itself through the actions of the National Council of Advertising Self-Regulation that are based mainly on the laws established by the Brazilian Code of Advertising Self-Regulation and its annexes. However, this system of advertising self-regulation still has some deficiencies that hinder its effectiveness